Pengaruh Profitabilitas, Pajak dan Ukuran Perusahaan Terhadap Transfer Pricing (Studi pada Perusahaan Sektor Tambang Sub Sektor Tambang Batubara yang terdaftar di Bursa Efek Indonesia) - Lisfiana, Lisfiana; Andrianto, Wahyu (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
. This study aims to examine and analyze the effect of profitability, taxes and company size on transfer pricing. The data used is secondary data in the form of financial statements of companies listed on the Indonesia Stock Exchange and obtained from the website www.idx.co.id. The population in this study is the mining sector companies in the coal mining sub-sector which are listed on the Indonesia Stock Exchange in 2012-2021 and were collected using a purposive sampling method. The samples obtained were 5 sample companies with a total of 22 observations. This research uses a descriptive method with panel data regression analysis. The results of testing the hypothesis in this study indicate that Profitability has a positive and not significant effect on Transfer Pricing, Taxes have a positive and significant effect on Transfer Pricing and Company Size has a positive and insignificant effect on Transfer Pricing